LEGAL ANALYSIS OF MANGROVE DAMAGE COMPENSATION WITH ECONOMIC VALUATION IN BINTAN - Lia Nuraini; Henky Irawan; Rizki Yuli Sari (Universitas Internasional Batam, 2022)
Bintan, the only conservation area at the district level, was established through the Regent's Decree No. 58/II/2009 and has an area of ​​472,905 ha, with a fairly high area of ​​mangroves and seagrass beds, especially in the southern region of Bintan Island. One interesting and sustainable phenomenon on Bintan Island is that beach destruction is often found in the form of lumps of dirty oil (sludge oil) during the north wind season along the northern coast of Bintan Island, stretching from Lagoi beach to Berakit beach. This study discusses the legal analysis of mangrove damage compensation with the economic valuation in Bintan. Research method This research uses empirical juridical research with qualitative and quantitative data types, from a qualitative perspective analyzing the legislation on the protection of mangrove ecosystems, and quantitative data analysis to measure the level of damage to mangroves in the Bintan area. The perpetrators of mangrove destruction can be subject to strict liability which imposes proof on the perpetrators. To provide a deterrent effect and save the environment as well as economic losses to Mangroves. Based on Ministerial Regulation Number 7 of 2014 concerning Environmental Losses Due to Pollution and/or Environmental Damage, describes community losses due to environmental damage, namely those that have an impact on community losses. Economic valuation of compensation due to mangrove destruction. As an ecotourism area in Bintan Regency, it can be calculated using the travel cost method, so that the action of the valuation in 1 month is as follows: Pengudang Village Tourism Rp. 20,000,000, Teluk Sebong Village Tourism Rp. 2,000,000, Penaga Village Tourism Rp. 29,040. 000, Lagoi Tourism Rp 834,000,000. The economic valuation due to mangrove damage in Bintan experienced by marginal fishermen is estimated at IDR 2,600,000 per month.